Pengembangan Aplikasi Eye Controlled Health Communication Board Pada Perangkat Android - Yusuf Hendrawan; Herman Tolle; Lutfi Fanani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Health Communication Board (HCB) is a tool that commonly used to aid communication issue between doctor or nurse with a patient who can't speak normally. HCB contains a set of illustration that represent action and some basic patient needs. To use HCB, the patient will be asked to point any illustration that represent what the patient wants to tell. But, this might become a problem if the patient also experiences motor impairment related to hand function. Which makes the patient unable to point to any illustration listed on the HCB, so that HCB become useless. In this research, an application that have the same function and mechanism as HCB will be developed. This application will be able to be controlled by using eye movements, so that patient with motor impairment will be able to use it. The result of validation testing using black box method produce a 100% conformity level which indicates that all the function is running as expected. Then, compatibility testing produces a score of 100% which indicates that the application is able to run normally when used in different devices with different API levels. For the usability testing related to respondent success rate when performing a set of given tasks, the application is able to produce a value of 90%. While for the usability testing related to respondent satisfaction using System Usability Scale (SUS), the application is able to produces a score of 84 which indicates that the application is able to deliver a good satisfaction level to its respondent by getting a B grade.